Metonymic Use of Proper Names as the Window to American Popular Culture - Muhammad Adam; Dita Dewi Palupi (Humanitatis : Journal of Language and Literature, 2023)
The study of proper name metonymy still needs more attention than metaphors, particularly the one related to creative metonymy from popular culture. Due to such rationale, this study examines how the proper names of famous American athletes are utilized as metonymy in English. The study objective is to identify the frequency, range period, and context or source of the metonymic use. In accomplishing this goal, three well-known American athletes become the focus of this study: Michael Jordan, Babe Ruth, and Muhammad Ali. The study is mainly qualitative, with simple quantitative analysis to measure the frequency. The data source was the Corpus of Contemporary American English (COCA), then the collected data from the three athletes were analyzed for their metonymic use. The analysis discovered that Michael Jordan became the most famous athlete with 67 usages, 58 of which were metonymic, followed by Babe Ruth with 23 usages and 21 metonymic use, and Muhammad Ali with all 18 data as metonymic. The characteristic or metonymic concepts attached to those famous names were uniquely dissimilar; Michael Jordan was associated with greatness, Babe Ruth was related to excellence, and Muhammad Ali was linked to magnificence. The field of context for these names’ utilization was not only from sports but also extended to social, scientific, art, business, law, and political areas. Meanwhile, the periods of use range from 1992 to 2018, with various sources from movies, magazine and newspaper news, TV news, and blogs. This study highlights how cultural aspects and cognition are essential in language expression, indicating how the dynamic change in society affects the dynamic shift in language expression.